Nuclear SSR markers for Miscanthus, Saccharum, and related grasses (Saccharinae, Poaceae)(1) - Hodkinson, Trevor R. (Botanical Society of America, 2013)
• Premise of the study: We developed nuclear simple sequence repeat (SSR) markers for the characterization of the biomass crop Miscanthus, especially M. sacchariflorus, M. sinensis, and M. ×giganteus, and tested for cross-species amplification. • Methods and Results: Twenty-nine SSR markers (di- and tetranucleotide repeats) were developed from DNA sequences obtained from 192 clones from an enriched genomic library of M. sinensis. All markers were successfully amplified in M. sacchariflorus, M. sinensis, and M. ×giganteus, and 19 amplified across a broad range of Miscanthus species. Polymorphism information content and expected heterozygosity values (19 locus sample) were 0.88 and 0.89, respectively, for M. sinensis, 0.48 and 0.54 for M. sacchariflorus, and were the lowest in M. ×giganteus (0.33, 0.41). Thirteen out of 19 primer pairs showed cross-species amplification in non-Miscanthus sensu stricto taxa. • Conclusions: The new set of 29 SSR markers will be of high value for characterizing Miscanthus germplasm collections, for prebreeding, and for assessing variation in natural populations.